2015
DOI: 10.1534/genetics.115.182071
|View full text |Cite
|
Sign up to set email alerts
|

Imputing Genotypes in Biallelic Populations from Low-Coverage Sequence Data

Abstract: Low-coverage next-generation sequencing methodologies are routinely employed to genotype large populations. Missing data in these populations manifest both as missing markers and markers with incomplete allele recovery. False homozygous calls at heterozygous sites resulting from incomplete allele recovery confound many existing imputation algorithms. These types of systematic errors can be minimized by incorporating depth-of-sequencing read coverage into the imputation algorithm. Accordingly, we developed Low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 37 publications
1
74
0
Order By: Relevance
“…Irrespective of the method evaluated, we observed heterozygous under-calling in animals that have been sequenced at low coverage, i.e., heterozygous variants were erroneously genotyped as homozygous due to an insufficient number of sequencing reads supporting the heterozygous genotype [10,[45][46][47]. In agreement with previous studies [2,5], Beagle imputation improved genotype concordance and reduced heterozygous under-calling particularly in cattle that had been sequenced at low coverage.…”
Section: Discussionsupporting
confidence: 88%
“…Irrespective of the method evaluated, we observed heterozygous under-calling in animals that have been sequenced at low coverage, i.e., heterozygous variants were erroneously genotyped as homozygous due to an insufficient number of sequencing reads supporting the heterozygous genotype [10,[45][46][47]. In agreement with previous studies [2,5], Beagle imputation improved genotype concordance and reduced heterozygous under-calling particularly in cattle that had been sequenced at low coverage.…”
Section: Discussionsupporting
confidence: 88%
“…Given the results obtained with simulated and real data, we recommend the use of NOISYmputer to impute noisy or high-quality GBS or WGS data. LB-Impute or Tassel-FSFHap can also be used for imputation of high-quality data, with a preference for LB-Impute in case of very low-coverage (< 0.4 X), as discussed in (Fragoso et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…To test NOISYmputer and other methods' accuracy on real data, we used the high-quality Rice_GBS dataset. We compared map sizes to the map obtained with LB-Impute combined with BP-Impute and a custom R script that selects the most probable genotype, as extensive testing on this dataset showed that this method provided accurate imputation (Fragoso et al, 2016.…”
Section: Methods For Algorithm Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructing linkage maps using sequencing data is complicated by the presence of two types of missing data that can result when the sequencing depth is low. The first is a missing genotype resulting from no alleles being called, while the second consists of a heterozygous genotype being called as homozygous due to only one of the parental alleles being sequenced at a particular locus (Fragoso et al . 2016; Dodds et al .…”
mentioning
confidence: 99%